Case report: One case of umbilical vein thrombosis in the second trimester with associated portal vein thrombosis after childbirth - Dai, Wei-Wei; Hou, Qi-Shu; Yang, Lian-Hua; Chen, Shang-Qin; Ye, Ji-Feng (Frontiers in Medicine, 2023)
Background Umbilical vein thrombosis is a rare pregnancy complication, that is difficult to detect prenatally but can lead to poor fetal outcomes. Case presentation We described a 33-year-old primiparae who was identified as having umbilical vein thrombosis by ultrasound at 21 weeks gestation, and the neonate was found to have a portal vein thrombus after delivery. Following enoxaparin anticoagulant therapy, the thrombus disappeared within 4 weeks. No thrombus formation occured during the 10-month follow-up, and the baby was in excellent clinical condition. Conclusion Owing to the poor fetal outcomes related to umbilical thrombosis, pay attention to abnormal clinical signs during prenatal ultrasound, fetal heart monitoring and counting fetal movements can help in the early identification of umbilical cord thrombosis.The findings highlight the importance of regular prenatal ultrasound evaluation, enabling early detection and monitoring of any anomalies or vascular abnormalities related to the fetal umbilical vein. Further research is warranted to explore the clinical implications and long-term outcomes associated with these findings.